A Polysomnographic Study of Parkinson’s Disease Sleep Architecture - Daniel Martinez-Ramirez; Sol De Jesus; Roger Walz; Amin Cervantes-Arriaga; Zhongxing Peng-Chen; Michael S. Okun; Vanessa Alatriste-Booth; Mayela Rodríguez-Violante (Parkinson's Disease)
Sleep disturbance is a common nonmotor phenomenon in Parkinson’s disease (PD) affecting patient’s quality of life. In this study, we examined the association between clinical characteristics with sleep disorders and sleep architecture patterns in a PD cohort. Patients underwent a standardized polysomnography study (PSG) in their “on medication” state. We observed that male gender and disease duration were independently associated with obstructive sleep apnea (OSA). Only lower levodopa equivalent dose (LED) was associated with periodic limb movement disorders (PLMD). REM sleep behavior disorder (RBD) was more common among older patients, with higher MDS-UPDRS III scores, and LED. None of the investigated variables were associated with the awakenings/arousals (A/A). Sleep efficiency was predicted by amantadine usage and age, while sleep stage 1 was predicted by dopamine agonists and Hoehn & Yahr severity. The use of MAO-B inhibitors and MDS-UPDRS part III were predictors of sleep stages 2 and 3. Age was the only predictor of REM sleep stage and gender for total sleep time. We conclude that sleep disorders and architecture are poorly predictable by clinical PD characteristics and other disease related factors must also be contributing to these sleep disturbances.